PERAN YAYASAN SHODIQUL MUBARAK DALAM PERENCANAAN SEKOLAH DI SDIT ALMUBARAK SCHOOL GOWA - St Zahidatul U'la; Mus, Sumarlin; Ansar, Ahlun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of Yayasan Shodiqul Mubarak (a private educational foundation) in school planning at SDIT Almubarak School Gowa. The research focuses on four main dimensions, namely the determination of strategic direction, school program planning, resource planning, and budget and financing planning. This study used a descriptive qualitative approach. Data were obtained through observation, interviews, and documentation involving the foundation board, the school principal, teachers, and parents as sources of information. The results show that the foundation plays an important role in determining strategic direction through its involvement in formulating the vision, mission, and goals of the school, setting program priorities, and synchronizing school policy with the foundation's direction. In school program planning, the foundation approves, supports, and evaluates programs designed by the school so that they meet the needs of learners and the goals of the institution. In resource planning, the foundation determines the need for educators, develops teacher competence, and provides educational facilities and infrastructure. Meanwhile, in budget and financing planning, the foundation acts as decision maker, financial controller, and guarantor of the sustainability of school financing through budget ratification, supervision of fund allocation, partnership development, and determination of priority scale. This study concludes that the role of the foundation in school planning is strategic, coordinative, and sustainable in supporting the effectiveness of education management at SDIT Almubarak School Gowa. Kata Kunci: Peran Yayasan, Perencanaan Sekolah, Penetapan Arah, Program Sekolah, Sumber Daya, Anggaran dan Pembiayaan.